ANALISIS PEMBIAYAAN BERMASALAH DI BANK WAKAF MIKRO PADA MASA PANDEMI COVID-19 (Studi Kasus di Bank Wakaf Mikro Al Fithrah Surabaya) - Ahmad Habib Mustofa (Universitas Muhammadiyah Surabaya, 2022)
This study aims to identify and analyze non performing financing at Bank Wakaf Mikro (BWM) Al Fithrah during the covid-19 pandemic. This type of research is descriptive qualitative using case study method at BWM Al Fithrah Surabaya. Research data was collected by direct observation and interviews with manager, supervisor, and customers at BWM Al Fithrah Surabaya regarding non performing financing during the Covid-19 pandemic, added with documents and financial reports. The data was processed by researcher, validated by triangulation techniques and analyzed with a descriptive-qualitative mindset. The results of the study conclude: Firstly, the increasing ratio of non performing financing during the Covid-19 pandemic in 2020 was caused by declining customerâ€™s income and the accompaniment named Halaqah Mingguan (HALMI) activities being temporarily suspended. Secondly, the trend of non performing financing ratio decreased during the Covid-19 pandemic in 2021 because HALMI activities had been implemented again, supported by regular payments from customers due to their business innovations that made their business run as usual, although the non performing financing Â level was still relatively high due to the payment arrears from HALMI Barokah group which was disbanded during the covid-19 pandemic in 2020. Suggestions from researchers are: Firstly, HALMI should still be implemented in any situation, because it has been proven successful in minimizing non performing financing. Secondly, providing knowledge to customers about the importance of business innovation. Third, provide references and training so that customers will be able to expand their business.Keywords: Non Performing Financing, Covid-19 Pandemic, Bank Wakaf Mikro.